2000
DOI: 10.1089/107999000750053807
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Specific CD4+and CD8+Immune Responses Are Generated with a gp120-Depleted, Whole-Killed HIV-1 Immunogen with CpG Immunostimulatory Sequences of DNA

Abstract: We examined the adjuvant effects of a synthetic CpG oligodeoxynucleotide immunostimulatory sequence (ISS) using a whole-killed, gp120-depleted HIV antigen (HIV-1 antigen) in a Lewis rat model. We hypothesized that HIV-1-specific CD4(+) T helper (Th) immune responses could be enhanced when an ISS was combined with an HIV-1 antigen in incomplete Freund's adjuvant (IFA). We also reasoned that if such Th responses were sufficient, such a combination might also induce HIV-specific CD8(+) T cell immune responses. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…This was the first study to systematically assess the effect of cryopreservation on T cell functionality using ELISPOT: a key finding from this study was that the addition of chilled washing medium to chilled cells can be highly detrimental to PBMC viability (Figure 1 in that publication). ELISPOT provides a reliable quantitative approach to assess functionality of diverse immune cell types including T cells of both CD4 and CD8 lineages [29,30,31]. We and others have utilized ELISPOT effectively to assess immunogenicity of both candidate- and licensed vaccines [5,26,32].…”
Section: Discussionmentioning
confidence: 99%
“…This was the first study to systematically assess the effect of cryopreservation on T cell functionality using ELISPOT: a key finding from this study was that the addition of chilled washing medium to chilled cells can be highly detrimental to PBMC viability (Figure 1 in that publication). ELISPOT provides a reliable quantitative approach to assess functionality of diverse immune cell types including T cells of both CD4 and CD8 lineages [29,30,31]. We and others have utilized ELISPOT effectively to assess immunogenicity of both candidate- and licensed vaccines [5,26,32].…”
Section: Discussionmentioning
confidence: 99%
“…Montanide ISA-51 is a mineral oil based adjuvant and has been shown to increase immune responses nonspecifically [2,34]. CpG-ODN is also among the most frequently used experimental adjuvant; this adjuvant stimulates dendritic cells through Toll-like receptor (TLR) 9, inducing cell maturation and enhancing antigen presentation and Th1 responses [25,26,38]. In addition, CpG-ODN up-regulates the expression of TAP (transporter associated with antigen presentation) in a type I interferon-dependent manner, resulting in induction of CTL responses independently of CD4+T cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that cytosine‐phosphorothioate‐guanine dinucleotide (CpG) ISS of DNA are naturally occurring unmethylated nucleotide sequences shown to stimulate B cells, dendritic cells and macrophages 6 . These sequences have been used, either alone or in combination with various adjuvants, to stimulate strong CD4 T helper immune responses 7 as well as CD8 T‐cell responses 2,8 . Multiple studies suggest that cell‐mediated immune responses, which include IFN‐γ production, cytotoxic T lymphocytes (CTLs) and CD8 antiviral suppressive factors, including β‐chemokines, may be associated with slower disease progression and prevention of disease 9–13 .…”
Section: Discussionmentioning
confidence: 99%
“…A vaccine may have an important role in preventing pediatric human immunodeficiency virus‐1 (HIV‐1) infection if protective immunity can be established during the neonatal period. It has previously been demonstrated that the combination of a gp120‐depleted, whole‐killed antigen in incomplete Freund's adjuvant (IFA) with immunostimulatory sequences (ISS) was a more potent stimulator of an antigen‐specific T helper 1 (Th1) type immune response and β‐chemokines than antigen and ISS or antigen and IFA 1–3 . We hypothesized that a protective immune response in the neonate might require maternal immunization, in order to develop passive antibody‐mediated immunity, followed by neonatal immunization, in order to induce cell‐mediated immune responses.…”
Section: Introductionmentioning
confidence: 99%